Ontogenetic analysis of siliceous cell wall formation in Triparma laevis f. inornata (Parmales, Stramenopiles). Issue 1 (19th November 2018) - Yamada, Kazumasa; Katsura, Hirotaka; Noël, Mary‐Hélène; Ichinomiya, Mutsuo; Kuwata, Akira; Sato, Shinya; Yoshikawa, Shinya
Abstract : Triparma laevis f. inornata is a unicellular alga belonging to the Bolidophyceae, which is most closely related to diatoms. Like diatoms, T. laevis f. inornata has a siliceous cell wall. The cell wall of T. laevis f. inornata consists of four round plates (three shields and one ventral plate) and one dorsal and three girdle plates. But, unlike diatoms, T. laevis f. inornata cells can grow when concentrations of silica are depleted. We took advantage of this ability, using TEM to study the ontogeny of the siliceous plate, pattern center formation, and development. Two types of pattern centers (annulus and sternum) were observed in the early and middle stage of plate formation. During their formation, the annuli were initially crescent‐shaped but eventually their ends fused to make a ring. Only outward silica deposition of the branching ribs occurred on the growing annulus until it became a ring, resulting in an unfilled circle inside the annulus. The pattern center of the shield plate was always an annulus, but in ventral plates both annulus and sternum were observed. The annuli and sterna in T. laevis f. inornata round plates were very similar to the annuli and sterna in diatom valves. These results suggested that the round plates of Parmales are homologous to diatom valves. This information on the plate ontogeny of T. laevis f. inornata provides new insights into the evolution of the siliceous cell wall in the Parmales and diatoms.